STUDI KUALITATIF HAMBATAN IMPLEMENTASI EVIDENCE-BASEDDUKUNGAN SELAMA PERSALINAN DI PRAKTIK MANDIRI BIDAN (PMB) WILAYAH KABUPATEN GUNUNGKIDUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2019 - Rizki Amalia; Mohammad Hakimi; Herlin Fitriana Kurniawati (LPPM - Universitas Muhammadiyah Banjarmasin, 2019)
Evidence-based is an effective strategy to improve the quality of midwifery care. The aim of this study is to explore in depth the barriers to the implementation of evidence-based support during normal labor at Praktik Mandiri Bidan (PMB). This research is a qualitative research with a phenomenological descriptive approach. Participant selection uses a purposive sampling technique (convinience sampling). Data collection using in-depth interviews and observations. Analysis of the data used is thematic analysis. The results of this study there are three barriers to implementation of support during normal labor, namely barriers from the family, barriers from patients and husbands, and lack of knowledge of patients and families about support during labor. It is difficult to implement the practice according to evidence-based, there are barriers that occur when implementing it. Health professionals are expected to increase the provision of education to patients and families about support during labor.